Women Leadership In Merauke Regency - Fitriani Fitriani; Rinno Bahari Adi Pratama; Nur Jalal (Universitas Musamus, Merauke, Papua, 2019)
This study aims to provide an overview of the types of leadership of women to lead successfully in Merauke Regency, especially the village head, namely Marga Mulya Village, Semangga District, and the factors that most influence the leadership of women village leaders. This research is a qualitative descriptive study, collecting data from the results of 10 informant interviews and field observations. The results of this study (1) found that the type of female leadership possessed was inclined to use the type of leadership by looking at the characteristics of what work would be done. Then there is a combination of 2 (two) styles of women's leadership, namely feminine-masculine and transformational-transactional, (2) The factor that most influences the leadership of village head women, is the good personality factor of the Village Head, in carrying out his leadership duties. And then followed by factors of leadership characteristics and expectations of leaders and colleagues and the community they lead.